The Relationship Between Parental Knowledge, Parenting Style, and Nutritional Status with Cognitive Development in Children Aged 4–6 Years - Hartono, Ali; Lestari, Indri Puji; Maryana, Maryana (Inspirasi Foundation, 2025)
Introduction: Early childhood is a critical period for cognitive growth, where development is strongly influenced by environmental and parental factors. Parents’ knowledge, parenting patterns, and nutritional status play a major role in shaping children’s cognitive abilities during this stage. Objective: Child growth and development encompass two aspects: growth and development. This growth is seen through increases in size and weight, such as height and weight gain. Development is defined as a progressive series of regular changes, focusing more on psychological and intellectual development. Children's cognitive development is part of the growth and development process. The purpose of this study is to determine the relationship between the level of knowledge, parenting patterns, and nutritional status with cognitive development in early childhood aged 4-6 years at Cahaya Mulia PAUD, Pebuar Village, West Bangka Regency in 2025. Method: This research method was carried out using Cross Sectional and Chi Square test with the results in the form of univariate analysis and bivariate analysis. The population in this study were students at PAUD Cahaya Mulia, Pebuar village, Jebus district in 2024. The sample of this study was all students totaling 30 respondents. Result: The results of the study showed that there was a relationship between knowledge (ρ = 0.002), parenting patterns (ρ = 0.029) and nutritional status (ρ = 0.018) with the cognitive development of children at PAUD Cahaya Mulia, Pebuar village, Jebus district in 2025 Conclusion: The conclusion is that cognitive development is influenced by various factors including knowledge, parenting patterns, and nutritional status. Each factor has a significant relationship.